Correlation Between the Responses to Growth Hormone (GH) Treatment During Childhood and Adulthood in a Monocentric Cohort of GH-Deficient Patients - Thilmany, Sarah; Mchirgui, Leila; Brunelle, Chloé; Beauloye, Véronique; Maiter, Dominique; Alexopoulou, Orsalia (Hormone and Metabolic Research, 2018)
Our aim was to analyze a cohort of patients with childhood-onset growth hormone deficiency (GHD) to evaluate if there is some correlation between the response to GH treatment during childhood and adulthood, respectively. This was an observational retrospective monocentric cohort study of 47 patients treated with GH during childhood and adulthood. Changes in growth parameters during childhood were compared with the increase of IGF-I z-score and other indexes of GH response (body composition, lipid profile) after 1 year of treatment in adulthood. The only significant positive correlation was observed between final growth velocity during the last year of childhood GH treatment and increase in IGF-I z-score in GH-treated adults (r=0.592, p=< 0.01). No correlation was observed between growth-promoting effects of GH as child and metabolic changes induced by GH as adult. We also observed a negative correlation between weight at the end of childhood GH treatment and the IGF-I response during first year of treatment in adults (r=− 0.335, p <0.05). No significant positive correlation could be observed between the main parameters that evaluate response to GH treatment in children and adults. However, the final growth velocity, which may be considered as one of the main criteria of end of GH treatment in children, was identified as parameter that could predict future response to GH treatment in adulthood.
Keywords: GH responsiveness; growth velocity; IGF-I; body composition